Deportation Ghettoes in Mali: Expelled Migrants Between State Exclusion and Self-Organization - (:unkn) unknown (My University, 2016)
This chapter examines three ‘ghettoes’ set up by African migrants in Mali after their expulsion from Algeria. These are respectively located in Tinzawaten, at the border with Algeria; in Gao, along the route and in Bamako, the capital city and a hub of regional migrations. The chapter explores the essential meanings and functions of ghettoes in relation to expulsion, representing them not only as places of exclusion and marginalization but also of autonomy, solidarity and resistance. As expulsion from Algeria largely reflects European pressures on Northern African states to prevent African migrants from reaching Southern Europe, the chapter also contributes to a more nuanced understanding of the spatial reconfigurations induced, though not entirely determined, by the externalization of European borders into Africa. It equally highlights the role of African contexts and migrants in forging particular political cultures in response to such border regimes.
Keywords: African Research